Tyrosine Kinase Inhibitors' Newly Reported Endocrine Side Effect: Pazopanib-Induced Primary Adrenal Insufficiency in a Patient With Metastatic Renal Cell Cancer - Ghada Elshimy MD; Anand Gandhi MD; Rong Guo MD; Ricardo Correa MD, EsD (SAGE Publishing, 2020)
Tyrosine kinase inhibitors (TKIs) have been used in the treatment of multiple types of cancer. Pazopanib is one of the TKIs and is considered a first-line treatment for adult patients with metastatic renal cell carcinoma. Many endocrine-related adverse effects have been noted with the use of TKIs including hypothyroidism, vitamin D deficiency, altered bone density, secondary hyperparathyroidism, abnormal glucose metabolism, gynecomastia, and hypogonadism. Subclinical glucocorticoid deficiency and adrenal insufficiency have been reported with the use of TKIs in only a few cases so far; thus, its true prevalence and clinical significance have yet to be fully elucidated. The mechanism is still not fully understood; however, adrenal toxicity with hemorrhage and/or necrosis of the adrenal glands has been observed in studies. In this article, we describe the first reported case of pazopanib inducing primary adrenal insufficiency in a patient with metastatic renal cell carcinoma diagnosed after the exclusion of all other causes of primary adrenal insufficiency.